2014
DOI: 10.1016/j.pain.2014.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Cold hypersensitivity increases with age in mice with sickle cell disease

Abstract: Sickle cell disease (SCD) is associated with acute vaso-occlusive crises that trigger painful episodes and frequently involves ongoing, chronic pain. Additionally, both humans and mice with SCD experience heighted cold sensitivity. However, studies have not addressed the mechanism(s) underlying the cold sensitization, nor its progression with age. Here we measured thermotaxis behavior in young and aged mice with severe SCD. Sickle mice had a marked increase in cold sensitivity measured by a cold preference tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
54
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 60 publications
(99 reference statements)
8
54
1
Order By: Relevance
“…These results are in contrast with the heat pain hyperalgesia and light touch allodynia reported in SCD mice and heat pain hyperalgesia in children with SCD [12, 18, 21, 30, 31]. However, our results are similar to another QST study of adults with SCD, which likewise did not show increased heat pain thresholds [13].…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…These results are in contrast with the heat pain hyperalgesia and light touch allodynia reported in SCD mice and heat pain hyperalgesia in children with SCD [12, 18, 21, 30, 31]. However, our results are similar to another QST study of adults with SCD, which likewise did not show increased heat pain thresholds [13].…”
Section: Discussioncontrasting
confidence: 85%
“…QST in SCD shows increased sensitivity to painful stimuli [12, 1821, 2630] which is heightened by age [18, 30, 31]. [27].…”
Section: Introductionmentioning
confidence: 99%
“…[49] Research thus far shows no differences in pain behavior between HBSS-BERK and Townes mice. Pain hypersensitivity also increases with age in SCD mice, [50] which correlates with the phenomena observed in SCD patients. [19] …”
Section: Animal Models Of Scd-associated Painsupporting
confidence: 64%
“…In an ex-vivo saphenous nerve preparation from HBSS-BERK and control mice, Zappia et al found that HBSS-BERK C-fibers responded at warmer temperatures when compared to control fibers during a decreasing temperature ramp from 32°C to 2°C (19.2 ± 1.2 °C vs. 14.6 ± °C). [50] This could represent sensitization of peripheral afferent terminals to cold stimuli as the control fibers can withstand colder temperatures without firing, thereby explaining cold hypersensitivity behavior observed in SCD mice. In a separate study of HBSS-BERK mice, mechanical allodynia was found to result from enhanced activation of mechanoreceptors.…”
Section: Potential Mechanisms Of Scd-associated Painmentioning
confidence: 99%
See 1 more Smart Citation